2019
DOI: 10.3389/fphar.2019.00592
|View full text |Cite
|
Sign up to set email alerts
|

Physician’s Knowledge of Appropriate Prescribing for the Elderly—A Survey Among Family and Internal Medicine Physicians in Nigeria

Abstract: Background: Prescription and use of inappropriate medications have been identified as a major cause of morbidity among the elderly. Several screening tools have been developed to identify inappropriate medications prescribed for elderly patients. There is dearth of information about the knowledge of Nigerian physicians regarding these screening tools and appropriate prescribing for the elderly in general. The primary objective of this study was to assess the knowledge of Nigerian physicians about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 36 publications
2
12
1
Order By: Relevance
“…The 2015 AGS‐Beers Criteria were adopted due to a lack of locally available validated criteria for appropriate prescribing to the elderly in Nigeria and South Africa at the time of this study . The correct response for each of the questions was awarded “1” and incorrect response “0” with the highest possible total score being seven.The respondents' knowledge was classified based on the total score as poor (0‐3), fair (4, 5) and good (6, 7) in line with a previous study . The respondents were divided into subgroups based on their socio‐demographics (eg, profession, gender, and length of practice) and differences in their mean knowledge and median scores were determined.…”
Section: Methodssupporting
confidence: 52%
See 4 more Smart Citations
“…The 2015 AGS‐Beers Criteria were adopted due to a lack of locally available validated criteria for appropriate prescribing to the elderly in Nigeria and South Africa at the time of this study . The correct response for each of the questions was awarded “1” and incorrect response “0” with the highest possible total score being seven.The respondents' knowledge was classified based on the total score as poor (0‐3), fair (4, 5) and good (6, 7) in line with a previous study . The respondents were divided into subgroups based on their socio‐demographics (eg, profession, gender, and length of practice) and differences in their mean knowledge and median scores were determined.…”
Section: Methodssupporting
confidence: 52%
“…This finding is, however, surprising considering that hypertension is one of the most common non‐communicable diseases with high morbidity and mortality in elderly Africans and HCPs are expected to be adequately knowledgeable about its pharmacotherapeutics . The finding of this present study, however, contradicts a previous report in Nigeria which indicated that physicians were adequately knowledgeable about the use of centrally acting hypertensives in the elderly …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations